Robust Image Watermarking Algorithm Based on ASIFT against Geometric Attacks - Chengyou Wang (Applied Sciences, 2018)
Image processing technology has been developed rapidly in recent years, and altering the content of an image is easy for everyone, but may be illegal for an attacker. Thus, it is urgent and necessary to overcome this problem to protect the integrity and authenticity of images. Watermarking is a powerful technique proposed to solve this problem. This paper introduces a robust image watermarking algorithm working in the wavelet domain, embedding the watermark information into the third level low frequency coefficients after the three-level discrete wavelet transform (DWT) and singular value decomposition (SVD). Additionally, to improve the robustness to geometric attacks, the affine-scale-invariant feature transform (ASIFT) is applied to obtain feature points which are invariant to geometric attacks. Then, features of acquired points between the watermarked image and the received image are used to realize the resynchronization to improve the robustness. Experimental results show that the proposed algorithm achieves great balance between robustness and imperceptibility, and is robust against geometric attacks, JPEG compression, noise addition, cropping, median filters, and so on.